Morphological, molecular and histopathological characterization of Plagiorhynchus crassicollis (Acanthocephala: Plagiorhynchidae) from a neotropical shorebird in Patagonia, Argentina - Capasso, Sofía Carolina (2021)
In this work we report Plagiorhynchus (Plagiorhynchus) crassicollis from Patagonia, Argentina. Specimens were collected from the small intestine of a charadriid shorebird with Neotropical distribution, the Two-banded Plover (Charadrius falklandicus). Both morphological and molecular characterization, plus pathological aspect of this species is provided. Plagiorhynchus (Plagiorhynchus) crassicollis is characterized by having a proboscis with 18–20 longitudinal rows of hooks and 11–14 hooks per row. Sequences of the small subunit (SSU) and large subunit (LSU) of the nuclear ribosomal DNA were obtained and compared with other sequences available in GenBank. Phylogenetic analyses inferred with each molecular marker consistently showed that P. (P.) crassicollis is sister taxa to Plagiorhynchus (Plagiorhynchus) aznari, a parasite of the long-billed curlew (Numenius americanus) from northern Mexico. Pathologic findings associated with the parasites include ulcerative enteritis, granulomatous inflammation, diffuse lymphocytic infiltration, serositis, and peritonitis. This record expands the host and geographical record of P. (P.) crassicollis, provide baseline information on its pathological aspects, and represents the first molecular characterization of P. crassicollis in the Neotropics.In this work we report Plagiorhynchus (Plagiorhynchus) crassicollis from Patagonia, Argentina. Specimens were collected from the small intestine of a charadriid shorebird with Neotropical distribution, the Two-banded Plover (Charadrius falklandicus). Both morphological and molecular characterization, plus pathological aspect of this species is provided. Plagiorhynchus (Plagiorhynchus) crassicollis is characterized by having a proboscis with 18–20 longitudinal rows of hooks and 11–14 hooks per row. Sequences of the small subunit (SSU) and large subunit (LSU) of the nuclear ribosomal DNA were obtained and compared with other sequences available in GenBank. Phylogenetic analyses inferred with each molecular marker consistently showed that P. (P.) crassicollis is sister taxa to Plagiorhynchus (Plagiorhynchus) aznari, a parasite of the long-billed curlew (Numenius americanus) from northern Mexico. Pathologic findings associated with the parasites include ulcerative enteritis, granulomatous inflammation, diffuse lymphocytic infiltration, serositis, and peritonitis. This record expands the host and geographical record of P. (P.) crassicollis, provide baseline information on its pathological aspects, and represents the first molecular characterization of P. crassicollis in the Neotropics.